The composition of the members of the administrative bodies of the mixed company of local economy - Bendjemila, Mohamed; Tayar, Mouna (Journal of Human Sciences, 2021)
Local mixed economy companies are considered as partnership contracts concluded between a partner in the public sector and another in the private sector, in order to achieve a general public interest for the inhabitants of a specific territory in many areas of life , such as housing, transport, training, health, etc. The majority of its capital is held by one or more local authorities, who must be members of their board of directors. Although it takes the form of a Shareholding company company provided for by commercial law, it is not subject to the same founding provisions, but in return it can follow the forms of management available, that is to say more ’a model, and the resulting legal effects, including membership in the board which differs from one model to another.